PATHOPHYSIOLOGY STROKE NON-HEMORRHAGIC ET CAUSA THROMBUS - Aji Kristianto Wijaya (E-Jurnal Medika Udayana, 2013)
Stroke is one of the most common cause of death worldwide and the third leading cause of death in the United States. Stroke composed 90,000 deaths of women and 60,000 men each year. In Indonesia, 8 of 1000 people suffered a stroke. Stroke is divided into two, non-hemorrhagic stroke and hemorrhagic stroke. Most of them (80%) is non-hemorrhagic stroke. Non-hemorrhagic stroke can be caused by thrombi or emboli. Understanding the pathophysiology of non-hemorrhagic stroke caused by a thrombus is very important in regard with providing appropriate patient management.